Links between foreign direct investment and human capital formation: Evidence from the manufacturing sector in India - Gunja Baranwal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper is related to the literature on the effect of foreign direct investment (FDI) on the labour market of host countries. Labour market literature has focused on the demand side of FDI; that is, increasing wage inequality by demanding more skilled workers or just increasing the overall average wages. On the supply side, FDI can enrich the skilled labour force of the host country by provision of on-the-job training or learning or through indirect technological spillover effects. This paper takes into account both these effects and tests for human capital formation effect of FDI in India for core manufacturing sector firms for the period 2001-15 using the Prowess database of the Centre for Monitoring Indian Economy. It also takes into account the endogeneity of decision-making on the part of foreign firms in locating FDI. Five different determinants of FDI are used: market size, distance from main market area, length of national highways, availability of non-agricultural land, and a cast and religion fractionalization index. The most significant factor determining FDI is market size and the distance from main market area and fractionalization index. Different dynamic panel data methods are used with static and dynamic generalized method of moments techniques. This study does not find any positive supply side human capital formation effects of FDI, but finds positive demand side effect of FDI of raising wage inequality and average wages. The results remain robust while taking into account heterogeneities at region, industry, size, and age of the firms.
Keywords: F24; J31; J24; 330; foreign direct investment; human capital; labour demand; labour supply; wages